Galilee in the late Second Temple and Mishnaic periods / 1 Life, culture, and society - Fiensy, David A. (Galilee in the late second temple and Mishnaic periods, 2014)
V. 1 Life, culture, and society Galilee and the historical Jesus in recent research Roland Deines -- The political history in Galilee from the first century BCE to the end of the second century CE Morten Hørning Jensen -- Religious practices and religious movements in Galilee: 100 BCE-200 CE Roland Deines -- The ethnicities of Galileans Mark A. Chancey -- The synagogues of Galilee Lee I. Levine -- Notable Galilean persons Thomas Scott Caulley -- Social movements in Galilee Richard Horsley -- The Galilean village in the late Second Temple and Mishnaic periods David A. Fiensy -- Household Judaism Andrea M. Berlin -- The Galilean house in the late Second Temple and Mishnaic periods David A. Fiensy -- Mortality, morbidity, and economics in Jesus' Galilee Jonathan L. Reed -- Education/literacy in Jewish Galilee: was there any and at what level? John C. Poirier -- The Galilean road system James F. Strange -- Urbanization and industry in Mishnaic Galilee Ze'ev Safrai -- Never the two shall meet?: urban-rural interaction in lower Galilee Agnes Choi -- Inner village life in Galilee: a diverse and complex phenomenon Sharon Lea Matilla -- Debate: was the Galilean economy oppressive or prosperous? Late Second Temple Galilee: socio-archaeology and dimensions of exploitation in first-century Palestine Douglas E. Oakman -- Late Second Temple Galilee: a picture of relative conomic health J. Andrew Overman -- Taxation and other sources of government income in the Galilee of Herod and Antipas Fabian Udoh